Evidence of Chinese Herbal Medicine Use From an Economic Perspective: A Systematic Review of Pharmacoeconomics Studies Over Two Decades - Xiong, Xiaomo; Jiang, Xiangxiang; Lv, Gang; Yuan, Jing; Li, Minghui; Lu, Z. Kevin (Frontiers in Pharmacology, 2022)
Objectives: Pharmacoeconomics evaluation (PE) is increasingly used in the healthcare decision-making process in China. Little is known about PE conducted in Chinese Herbal Medicines (CHMs). We aimed to systematically review trends, characteristics, and quality of PE of CHMS. Methods: We systematically searched both Chinese (CNKI, WanFang, and VIP) and English (Pubmed) databases. Studies were included if they were PE studies comparing both costs and outcomes between two or more interventions published in Chinese or English. Assessment of the quality of studies was conducted using the Quality of Health Economic Analyses (QHES) instrument. T-test and Chi-square tests were used to compare the studies before and after the first edition of China Guidelines for PE published in 2011, and between studies published in Chinese and English. Results: A total of 201 articles were included. There was an increasing trend of PE studies on CHMs during the study period. The top three studied diseases were central nervous system (CNS), mental, and behavioral disorders; cardiovascular diseases; and blood, immune and endocrine diseases. The average QHES score for the included studies was 63.37. Cost-effectiveness analysis (CEA) accounted for the majority (76.6%) of the included studies. Only a quarter of the articles (27.4%) were funded, and there were significantly more studies funded after the publication of China guidelines for PE. About 96.5% of studies did not specify evaluation perspectives and 89.6% of studies had a sample size of less than 300. Around half of the studies (55%) used incremental analysis, but only a few of them considered using a threshold. Half of the studies lacked sensitivity analysis. There was no significant improvement in the quality of studies published after the publication of China Guidelines for PE, and English articles had significantly higher quality than Chinese articles. Conclusions: This study identified several problems in PE studies on CHMs, including having small sample sizes, lacking necessary research elements, and using single evaluation methods. The quality of PE studies on CHMs was not sufficient. Researchers need to understand the standardized way to conduct PE studies and improve the quality and level of PE studies on CHMs.